Pemanfaatan Batang Pisang Fermentasi sebagai Pakan Tambahan dalam Ransum Ayam Kub Fase Finisher di Sekolah Tinggi Pertanian Flores Bajawa - Djawapatty, David; Mano, Wigberta N.; Ngaku, Maria Alfonsa (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Feed plays an important role in providing essential nutrients to livestock, meeting their basic needs for survival and productivity. Feed supply difficulties also occur in East Nusa Tenggara Province more specifically in Ngada Regency, Bajawa District. An effective solution to overcome the challenge of feed availability is to incorporate alternative feed ingredients. One type of agricultural waste that is commonly found is banana stems. Banana trees are widely found in tropical areas such as Indonesia, especially in areas that have many banana trees such as the Bajawa area. The cutting down of banana trees for fruit will produce more waste, such as leaves, stems, stumps, and banana peels, compared to the main product, which is banana pulp. The objectives of this study were to assess the quality of fermented feed produced from banana stems and to effectively utilize banana stem waste. This research was conducted at Flores Bajawa College of Agriculture. The research started in June-August 2024. The research material was about the utilization of fermented banana stems as additional feed in the ration of finisher phase KUB chickens. Banana stems were chopped as much as 30 kg (75% of fresh material) and rice bran 10 kg (25% of fresh material), water 3 liters, brown sugar 500 g, EM4 3 bottle caps. Fermentation of banana stems produced a protein content of 5. 4% and a crude fiber content of 16. 48%. The quality of fermented feed aroma produced is like alcohol, fragrant, yellowish brown color, no mold growth. The conclusion of making fermantasi animal feed made from banana stems is one of the efforts made to add economic value to farmers, in a situation of animal feed crisis. In addition, the content contained in banana stems is sufficient to meet the needs of KUB chickens